"Learn the Signs. Act Early.": Updates and Implications for Physical Therapists. Issue 4 (23rd October 2022) - Kretch, Kari S.; Willett, Sandra L.; Hsu, Lin-Ya; Sargent, Barbara A.; Harbourne, Regina T.; Dusing, Stacey C.
Abstract : Purpose: In early 2022, the Centers for Disease Control and Prevention (CDC) updated their developmental surveillance milestone checklists. The purpose of this article is to clarify and interpret the updates from a physical therapist perspective and to discuss implications of the new milestones for physical therapists. Summary of Key Points: The CDC's updated checklists provide clear, consistent, easy to use, and evidence-based developmental milestones to prompt discussion with families. The new checklists do not represent a lowering of standards and will likely increase, not decrease, referrals for screening, evaluation, and services. Crawling has been removed from the milestone checklists, as the current evidence suggests that crawling is highly variable and not essential for development. Conclusions and Recommendations for Clinical Practice: The updated milestone checklists will facilitate bringing vital services to children who need them. Physical therapists should support our primary care colleagues in implementing this useful program.